"We'll be able to take care of ourselves" – A qualitative study of client attitudes toward implementing buprenorphine treatment at syringe services programs. Issue 4 (October 2021) - Frost, Taeko; Deutsch, Sarah; Brown, Shoshana; Lemien, Ellen; Cunningham, Chinazo O.; Fox, Aaron D.
Background: Syringe services programs (SSPs) complement substance use disorder treatment in providing services that improve the health of people who use drugs (PWUD). Buprenorphine treatment is an effective underutilized opioid use disorder treatment. Regulations allow buprenorphine prescribing from office-based settings, potentially including SSPs although few studies have examined this approach. Our objective was to assess the attitudes among PWUD toward the potential introduction of buprenorphine treatment in an SSP. Methods: In this qualitative study, we recruited 34 participants who were enrolled at a New York City-based SSP to participate in one of seven focus group sessions. The focus group facilitators prompted participants to share their thoughts in five domains: attitudes toward (1) medical clinics; (2) harm reduction in general; (3) SSP-based buprenorphine treatment; (4) potential challenges of SSP-based treatment; and (5) logistical considerations of an SSP-based buprenorphine treatment program. Four researchers analyzed focus group transcripts using thematic analysis. Results: Of the 34 participants, most were white (68%), over the age of 40 years old (56%), and had previously tried buprenorphine (89%). Common themes were: 1) The SSP is a supportive community for people who use drugs; 2) Participants felt less stigmatized at the SSP than in general medical settings; 3) Offering buprenorphine treatment could change the SSP's culture; and 4) SSP participants receiving buprenorphine may be tempted to divert their medication. Participants offered suggestions for a slow intentional introduction of buprenorphine treatment at the SSP including structured appointments, training medical providers in harm reduction, and program eligibility criteria. Conclusion: Overall, participants expressed enthusiasm for onsite buprenorphine treatment at SSPs. Research on SSP-based buprenorphine treatment should investigate standard buprenorphine treatment outcomes but also any effects on the program itself and medication diversion. Implementation should consider cultural and environmental aspects of the SSP and consult program staff and participants.